2019
DOI: 10.1177/0003489419858629
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Voice and Prognostic Markers for the Recovery of Vocal Fold Paralysis After Thyroid Surgery

Abstract: Objectives: This study is set to analyze clinicopathological factors predicting the recovery of unilateral vocal fold paralysis (UVP) in patients after thyroid gland surgery. The quality of voice was additionally assessed in these patients. Methods: The charts and videolaryngostroboscopy (VLS) examinations of 84 consecutive patients with a complete UVP after surgery of the thyroid gland were retrospectively reviewed. Patients were divided into 2 groups: patients who fully recovered from vocal fold paralysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Some of the patients who revealed asymmetric VFM under laryngofiberscopy still had good subjective voice performance, which has been mentioned previously (27,28). Reiter et al (29) reported that voice parameters did not significantly differ between patients with and patients without recovery from vocal cord paralysis at the end of a 12-month follow up. In the current study, the R Group and the U Group did not significantly differ in objective or subjective voice parameters in all follow-up periods.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Some of the patients who revealed asymmetric VFM under laryngofiberscopy still had good subjective voice performance, which has been mentioned previously (27,28). Reiter et al (29) reported that voice parameters did not significantly differ between patients with and patients without recovery from vocal cord paralysis at the end of a 12-month follow up. In the current study, the R Group and the U Group did not significantly differ in objective or subjective voice parameters in all follow-up periods.…”
Section: Discussionmentioning
confidence: 56%
“…Reiter et al. ( 29 ) reported that voice parameters did not significantly differ between patients with and patients without recovery from vocal cord paralysis at the end of a 12-month follow up. In the current study, the R Group and the U Group did not significantly differ in objective or subjective voice parameters in all follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies on laryngoscopy findings, predicting recovery of VFM, following thyroid operations are scarce. In a study by Reiter et al [21], the authors identify positive mucosal waves on the paralyzed side and a minimal glottic gap \ 3 mm seen at the first post-operative examination as positive predictive factors for recovery, while Choi et al [32] report the absence of compensatory movement of the normal side on videostroboscopy as an independent prognostic factor. None of the above studies included [32] or managed to correlate [21] IONM results and FFL findings to predict progression of transient VFP to permanent.…”
Section: Discussionmentioning
confidence: 99%
“…Although postoperative subjective voice impairments due to RLN paralysis usually improve over time, they may not return to normal [ 34 ]. Since early intervention confers a large benefit in patients with incomplete compensation [ 35 ], comprehensive voice assessment is mandatory, and voice therapy and interventions should be performed no longer than six–12 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%